2020
DOI: 10.1073/pnas.1922747117
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod and temperature separately regulate nymphal development through JH and insulin/TOR signaling pathways in an insect

Abstract: Insects living in the temperate zone enter a physiological state of arrested or slowed development to overcome an adverse season, such as winter. Developmental arrest, called diapause, occurs at a species-specific developmental stage, and embryonic and pupal diapauses have been extensively studied in mostly holometabolous insects. Some other insects overwinter in the nymphal stage with slow growth for which the mechanism is poorly understood. Here, we show that this nymphal period of slow growth is regulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…It can change the developmental trajectory to deal with different environments, which is also a strategy for adapting the environment. Like most insects, chironomid midge is also coordinately regulated by ecdysone and juvenile hormone from larva to pupa and to adult, juvenile hormone can prevent metamorphosis induced by ecdysone (Guo et al, 2019;Hu X. L. et al, 2019;Miki et al, 2020;Santos et al, 2019). The genes involved in biosynthesis of ecdysone and juvenile hormone which regulate insect development were also recognized inC. striatipennis.…”
Section: Gene Families Associated With Adaptive Evolutionmentioning
confidence: 99%
“…It can change the developmental trajectory to deal with different environments, which is also a strategy for adapting the environment. Like most insects, chironomid midge is also coordinately regulated by ecdysone and juvenile hormone from larva to pupa and to adult, juvenile hormone can prevent metamorphosis induced by ecdysone (Guo et al, 2019;Hu X. L. et al, 2019;Miki et al, 2020;Santos et al, 2019). The genes involved in biosynthesis of ecdysone and juvenile hormone which regulate insect development were also recognized inC. striatipennis.…”
Section: Gene Families Associated With Adaptive Evolutionmentioning
confidence: 99%
“…However, the environment can impact hormones that regulate growth. A recent study on the cricket Modicogryllus siamensis demonstrated that higher rearing temperatures lead to enhanced Insulin/TOR signaling, leading to faster growth rate (Miki et al, 2020). Insulin/TOR signaling, however, does not impact the number of instars in M. siamensis; instead, the timing of JH decline impacts the duration of the juvenile growth period in a photoperiod-dependent manner (Miki et al, 2020).…”
Section: Environmental Regulation Of Insect Metamorphic Hormonesmentioning
confidence: 99%
“…A recent study on the cricket Modicogryllus siamensis demonstrated that higher rearing temperatures lead to enhanced Insulin/TOR signaling, leading to faster growth rate (Miki et al, 2020). Insulin/TOR signaling, however, does not impact the number of instars in M. siamensis; instead, the timing of JH decline impacts the duration of the juvenile growth period in a photoperiod-dependent manner (Miki et al, 2020). Thus, body size determination appears to rely on a complex interaction of endocrine regulators that respond differently to distinct environmental cues.…”
Section: Environmental Regulation Of Insect Metamorphic Hormonesmentioning
confidence: 99%
“…Interestingly, freeze tolerance in the cricket Gryllus veletis requires shifts in both T b and photoperiod ( Toxopeus et al. 2019 ); and nymphal development in the cricket Modicogryllus siamensis depends on both photoperiod and temperatures pathways ( Miki et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%